Patient-reported outcomes after neoadjuvant therapy for rectal cancer: a systematic review. Issue 8 (August 2014) - Gavaruzzi, Teresa; Lotto, Lorella; Giandomenico, Francesca; Perin, Alessandro; Pucciarelli, Salvatore
<x xml:space="preserve">Abstract</x> Neoadjuvant therapy followed by total mesorectal excision is standard of care for locally advanced rectal cancer. However, this approach has been previously shown to be associated with high rate of morbidity and it may have a negative effect on patients' reported outcomes (PROs). In order to summarize findings on the effect of the neoadjuvant approach on PROs, we systematically reviewed articles published in the last five years. Thirty-five articles met the inclusion criteria. Ten articles compared the effect of surgery with and without neoadjuvant therapy, six articles compared different neoadjuvant therapies, ten articles reported on patients who were all treated with neoadjuvant therapy, and nine articles examined the effect of neoadjuvant therapy in the analyses. The results are summarized by function investigated and critically commented.